2019
DOI: 10.1111/trf.15169
|View full text |Cite
|
Sign up to set email alerts
|

Current state of transfusion in traumatic brain injury and associated coagulopathy

Abstract: Traumatic brain injury (TBI)‐induced coagulopathy has long been recognized as a significant risk for poor outcomes in patients with TBI, but its pathogenesis remains poorly understood. As a result, current treatment options for the condition are limited and ineffective. The lack of information is most significant for the impact of blood transfusions on patients with isolated TBI and in the absence of confounding influences from trauma to the body and limbs and the resultant hemorrhagic shock. Here we discuss r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 87 publications
1
10
0
3
Order By: Relevance
“…This strong association, albeit not statistically significant, requires additional investigation and represents research and clinical opportunities to evaluate the effect of whole blood transfusion on the blood brain barrier, platelet function, mitigation of coagulopathy, or other factors that may impact outcomes. 36,37 The strong association we reported is in agreement with previous studies, which have shown increased transfusion of plasma or platelets is associated with improved outcomes in traumatic brain injury patients. 38,39 Our study supports the concept that hemostatic resuscitation may also improve outcomes in traumatic brain injury patientsdnot just systemic bleeding.…”
Section: Discussionsupporting
confidence: 92%
“…This strong association, albeit not statistically significant, requires additional investigation and represents research and clinical opportunities to evaluate the effect of whole blood transfusion on the blood brain barrier, platelet function, mitigation of coagulopathy, or other factors that may impact outcomes. 36,37 The strong association we reported is in agreement with previous studies, which have shown increased transfusion of plasma or platelets is associated with improved outcomes in traumatic brain injury patients. 38,39 Our study supports the concept that hemostatic resuscitation may also improve outcomes in traumatic brain injury patientsdnot just systemic bleeding.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with earlier reported incidences of coagulopathy ranging between 10% and 97% in combined pediatric and adult populations after various types of isolated TBI. 7,20,25,28 Based on our review of patient data, we excluded any patients who had prehospital or ED fluid administration to ensure that any deranged coagulopathy observed from initial ED blood investigations was likely primary. The coagulopathy profile is not confounded by hypothermia in Singapore due to the equatorial effect.…”
Section: Discussionmentioning
confidence: 99%
“…6,29 Our study findings were consistent with those of both adult and pediatric studies demonstrating that trauma-induced coagulopathy is associated with increased disability, as measured by GOS-E Peds and mortality. 4,17,23,25,26 Many studies define unfavorable neurological outcome as a GOS-E Peds score of 1 to 4, which includes death. In the analysis of neurological outcomes for survivors, this would be a potential confounder, especially if TBI-associated coagulopathy was already a known predictor of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations